Levofloxacin induces erythrocyte contraction leading to red cell death - Hafiz Muhammad Aslam; Azka Sohail; Ammara Shahid; Maham Abdul Bari Khan; Muhammad Umar Sharif; Razia Kausar; Samia Nawab; Waqas Farooq; Dr. Kashif Jilani; Majeeda Rasheed (AboutScience Srl, 2024)
Background: Levofloxacin, a fluoroquinolone, is an extensively used antibiotic effective against both positively and negatively staining bacteria. It works by inhibiting bacterial topoisomerase type II and topoisomerase type IV, resulting in impaired DNA synthesis and bacterial cell death. Eryptosis is another term for apoptotic cell death of erythrocyte marked by cell shrinkage, phosphatidylserine (PS) flipping, and membrane blebbing. Methods: The intent of the present research was to look at the eryptotic effect of levofloxacin by exposing erythrocytes to therapeutical doses (7, 14 µM) of levofloxacin for 48 hours. Cell size evaluation, PS subjection to outside, and calcium channel inhibition were carried out to investigate eryptosis. Oxidative stress generated by levofloxacin was measured as a putative mechanism of eryptosis using glutathione peroxidase (GPx), superoxide dismutase (SOD), and catalase activities. Similarly, hemolysis measurements demonstrated levofloxacin's cytotoxic effect. Results: Our findings showed that therapeutic doses of levofloxacin can cause a considerable decline in antioxidant enzymes activities, as well as induce cell shrinkage, PS externalization, and hemolysis in erythrocytes. The role of calcium in triggering erythrocyte shrinkage was also confirmed. Conclusion: In conclusion, our findings showed that the indicated levofloxacin doses caused oxidative stress, which leads to erythrocyte death via eryptosis and hemolysis. These findings emphasize the importance of using levofloxacin with caution and the need for additional research to mitigate these side effects.